Takayasu’s arteritis diagnosed in a patient with Crohn's disease: An unpredicted correlation - Gülseren EVİRGEN ŞAHİN,; Semanur ÖZDEL,; Ferda ÖZBAY HOŞNUT,; Gökçe ÇINAR,; Hüsniye YÜCEL,; Meltem AKÇABOY, (Archives of Rheumatology, 2021)
Takayasu's arteritis (TA) and Crohn's disease (CD) are both immune-mediated, chronic, recurrent granulomatous inflammatory diseases that are rarely seen in children.[1,2] Here, we present an adolescent female patient with CD with severe upper gastrointestinal system involvement diagnosed as TA to guide the probable common pathophysiological pathways and to remind regarding the possibility of the coexistence of these two diseases. A 15-year-old girl was admitted to our clinic with dyspeptic complaints, diarrhea for two weeks, and weight loss. Her prenatal, natal, and postnatal history was uneventful. Her family history was unremarkable. Physical examination including growth parameters and pulses were in normal limits. Laboratory data revealed elevation of inflammatory markers. The upper endoscopy and colonoscopy presented multiple patchy and longitudinal mucosal aphthous ulcerations and cobblestone areas. Histopathological examination showed an increase of lamina propria cellularity, basal lymphoid aggregates, and epithelioid granuloma as well as crypt abscess formation. Clinical and histopathological findings were consistent with CD. The patient was initially treated with 2 mg/kg/day oral methylprednisolone. Azathioprine was added to corticosteroid therapy in follow-up. The corticosteroid therapy was tapered by the remission in third week. Over the course of two months, disease activity was unapparent with normal acute phase reactants. At the eighth month follow-up, acute phase indicators started to increase (erythrocyte sedimentation rate: 80 mm/hour, C-reactive protein: 92 mg/dL) in routine controls without any symptoms. All of the results were in normal ranges for the complete blood count, autoimmune markers, and endoscopic findings excluding disease activity. The patient had constitutional symptoms with unilateral neck pain with widespread sensitivity. Neck ultrasound revealed a stenosis of the right carotid artery. The magnetic resonance angiography imaging for right carotid artery showed diffuse wall thickening and 30-40% stenosis extending to the level of bifurcation (Figure 1). Clinical and laboratory features were consistent with TA. A written informed consent was obtained from the ethics committee and the parents of the patient. <f1> Crohn's disease and TA are both chronic granulomatous diseases with a course of remission and relapses. The coexistence of these two diseases rather than coincidence is associated with common features in etiopathogenesis.[3-5] The inflammation process is conducted by the similar cytokines like tumor necrosis factor-alpha and interleukin (IL)-6 in both diseases.[4,5] The fact that p40, the product of IL-12 associated with TA, is a subgroup of IL-23, one of the genes implicated in the pathogenesis of CD, suggests that both diseases have common genetic characteristics.[5] Granulomatous reaction and mononuclear inflammation are common histopathological features of both diseases.[4,5] Until now, few case reports have reported TA and CD in the same patient, though such coexistence has been hypothetically predicted to occur in only one in 10 billion individuals.[6,7] Primarily, it is important to be careful in terms of extra-intestinal involvement in CD and the findings of other autoimmune diseases in terms of the course of the disease and prevention of complications. Surely, TA, which is a rare association, should also be kept in mind in the presence of unexplained findings and non- symptomatic acute flares in patients with CD during the remission of the disease.